Special Purpose Vehicle Institutions: Their Business Natures and Accounting Implications - Ainun Na'im (Gadjah Mada International Journal of Business, 2006)
Special Purpose Vehicle (SPV) is an instrumental institution used for specific purposes by firms. The SPV is useful for tax planning, risk management, project financing and company restructuring. SPVs have benefits for economy and business, and involve usually large size of projects that vary from about US$100 to US$500 million per project. However, SPVs have also some bad records. Huge business, finance, and accounting scandals involve the use of SPVs. The drawbacks of SPVs are due to lack of regulatory measures relating the application of SPVs, so that SPVs are used for hiding identities, debts and hiding non-productive assets. SPVs are used to deceive investors so that they can not judge the value and risks of the firms and investments correctly.The huge financial and accounting scandals such as Enron involved the use of SPVs for not reporting or undervaluing debt and overvaluing net worth. In Indonesia, there are some transactions that are under public scrutiny that use SPVs, such as the sales of the government stocks of BCA Bank, and PT Indosat. There are also many successful and beneficial uses of SPVs in Indonesia as well, such as those in energy development, oil refinery, and telecommunication projects.